The Components of the Lesson Plan (RPP) Compiled by Students of German Department State University of Malang - Anastasia Agustina Weteng Weruin (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2020)
This research aims to describe the components of the lesson plan (RPP) compiled by students of German Department State University of Malang and used during carrying out Kajian Praktik Lapangan (KPL) in several high schools in the academic year 2019/2020. This research uses a descriptive qualitative research design. The data source of this research is the written data source, which are documents in the form of lesson plans that are compiled and used by five students of German Department 2016 who carry out the KPL in several high schools. The research data is in the form of verbal data about the overall description of information in each lesson plan. The technique used to collect data is the document study guidelines, while the technique used to analyze the data is the document analysis technique. The result showed that the 2013 curriculum’s RPPs compiled by German Department students were mostly in accordance with Permendikbud No. 22 of 2016. However, there are some deficiencies such us AR and AW not listing all 13 components of the lesson plans needed and in some lesson plans components, almost all authors does not explain in detail the information on each component of the RPP.